2004
DOI: 10.1088/0268-1242/19/6/016
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness of ZnO at low temperatures

Abstract: In situ Hall-effect measurements have been carried out on vapour-phase-grown, n-type ZnO irradiated with 1.0 and 1.5 MeV electrons in the [000-1] direction. The electrical properties change very little during irradiation at temperatures as low as 130 K, the lowest temperature presently attainable under 1 MeV, 0.3 µA cm −2 irradiation. It is concluded that long-term damage in ZnO is limited by defect annihilations that are rapid on the time scale of the experiment (<1 min), even at 130 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(58 citation statements)
references
References 12 publications
3
55
0
Order By: Relevance
“…[531][532][533][534][535] ZnO NW FETs were fabricated and irradiated with 35 MeV protons. 536 It was found that relatively low fluences in the range of ͑0.4-4͒ ϫ 10 12 protons/ cm 2 caused significant changes to the electrical characteristics of the FETs.…”
Section: B Implantation Of Compound Semiconductor Nwsmentioning
confidence: 99%
“…[531][532][533][534][535] ZnO NW FETs were fabricated and irradiated with 35 MeV protons. 536 It was found that relatively low fluences in the range of ͑0.4-4͒ ϫ 10 12 protons/ cm 2 caused significant changes to the electrical characteristics of the FETs.…”
Section: B Implantation Of Compound Semiconductor Nwsmentioning
confidence: 99%
“…The apparent radiation hardness remains when the irradiation is performed at a low temperature of 130 K, 22 indicating that the primary irradiation-induced compensating defects are mobile already at those temperatures. The microscopic origin of the radiation hardness of ZnO is not, however, well understood.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These properties, combined with other physical characteristics of ZnO such as the ability to grow single crystals, a low-power threshold for optical pumping, many possibilities for wet-chemical etching, and resistance to radiation damage, [1][2][3][4][5][6][7] further strengthen the device-based interest in this material. Important aspects of device fabrication include electrical isolation and selective-area doping, which are commonly achieved in the microelectronic industry by ion implantation.…”
mentioning
confidence: 97%